The Implementation of Artificial Intelligence in Islamic Religious Education and Its Impact on Students’ Religious Character at State Senior High School 1 Makassar - Arsyam, Muhammad; Zakirah, Zakirah (Scidac Plus, 2026)
This study aims to analyze the implementation of Artificial Intelligence (AI) in Islamic Religious Education learning and its influence on the development of students’ religious character at SMA Negeri 1 Makassar. The research is grounded in the increasing use of AI in educational processes, which presents both opportunities and challenges in internalizing religious values. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using thematic data reduction, data display, and conclusion drawing. The findings indicate that AI implementation occurs adaptively through educational chatbots, moral case analysis, and technology-assisted reflective discussions. AI enhances student engagement, contextual understanding of Islamic teachings, and digital responsibility awareness when guided by proper pedagogical supervision. However, unreflective use may lead to dependency and superficial value internalization. The study concludes that AI can support religious character formation when integrated ethically and systematically. Therefore, strengthening religious digital literacy and establishing school regulations are essential to ensure that AI utilization remains aligned with the goals of Islamic education.